Badass habits: cultivate the awareness boundaries, and daily upgrades you need to make them stick - Sincero, Jen (London John Murray (Hachette India), 2020)
Jen Sincero gets to the core of transformation: habits - breaking, making, understanding, and sticking with them like you've never stuck before.Badass Habits is a eureka-sparking, easy-to-digest look at how our habits make us who we are, from the measly moments that happen in private to the resolutions we loudly broadcast (and, erm, often don't keep) on social media. Habit busting and building goes way beyond becoming a dedicated flosser or never showing up late again--our habits reveal our unmet desires, the gaps in our boundaries, our level of self-awareness, and our unconscious beliefs and fears. Badass Habits features Jen's trademark hilarious voice and offers a much-needed fresh take on the conventional wisdom and science that shape the optimism (or pessimism?) around the age-old topic of habits. The book includes enlightening interviews with people who've successfully strengthened their discipline backbones, new perspective on how to train our brains to become our best selves, and offers a simple, 21 day, step-by-step guide for ditching habits that don't serve us and developing the habits we deem most important. Habits shouldn't be impossible to reset--and with healthy boundaries, knowledge of--and permission to go after--our desires, and an easy to implement plan of action, we can make any new goal a joyful habit.
Keywords: Motivation Book; Self-Help Book